Entre leitores (e) espiões: um estudo da metaficção no romance Sweet Tooth, de Ian McEWAN - Gomes, Caio Antônio de Medeiros Nóbrega Nunes (2017)
This dissertation proposes an analysis of metafiction in Ian McEwan’s novel Sweet Tooth, published in 2012. For that purpose, we will examine the movements this literary text makes towards literature itself – towards its production and reception conditions –, which characterizes a continuous process of reflecting upon fiction-making. Our theoretical framework encompasses studies published in the field of metafiction, be it in relation to its general principles or specific metafictional strategies activated in our analysis. Indeed, several metafictional mechanisms problematize fiction-making in McEwan’s novel, such as the parody of spy and detection narratives, the use of mise en abyme, and the metamedial representation of literature, that endow the narrative with a complex structure which will highly influence the reception process. Accordingly, our analysis focuses on how Sweet Tooth has its meanings constructed regarding the aesthetic phenomenon of metafiction. Our analysis is supported by critical and theoretical principles drawn especially from Bernardo (2010), Hutcheon (1980), Waugh (1984), in relation to the aesthetic phenomenon of metafiction, and from Hutcheon (1989) and Korkut (2005), regarding parody.